Analysis of the Building Structure for Mixed-Use Al-Amin Living Lab and Industrial Park in Sampe Cita Village, Kutalimbaru District - Hendra Fahruddin Siregar; Dadang Subarna; Melly Andriana, M; Ali Tami Purba (International Forum of Researchers and Lecturers, 2024)
A mixed-use building refers to the combination of several different functions in one building, such as residential, office, shopping, and recreational functions built on one site. Designing the structure of a mixed-use building requires careful planning and consideration of various factors such as functional needs, aesthetics, and energy conservation. Additionally, the design of mixed-use buildings includes various functions in one area. The floor slabs and roofs use plain reinforcing steel with a strength of Fy = 240 MPa (Ø8mm). Concrete cover is taken as 20 mm. The design results in several types of slab thicknesses according to the working loads that must be accommodated above them. Below are the moments acting on the floor slabs and roofs. Reinforcement calculations are carried out using the capacity strength design method according to SNI 2847-2019. The concept of capacity design refers to controlling the formation of plastic hinges at predetermined locations. The SAP2000 program can directly calculate the feasibility of structural dimensions and the required reinforcement area from the input program results. In the SAP2000 program, the concrete regulations used are those of the American Concrete Institute ACI-318-05/IBC 2003, which in some aspects differ from Indonesian concrete regulations SNI 2847-20219. Adjustments need to be made to comply with Indonesian regulations. Internal forces from the SAP2000 program are selected from load combinations that produce the maximum field moments and support moments at the column faces. Flexural and shear reinforcement of beams can be directly read from the SAP2000 program output in the form of the required reinforcement area information